Optimization of the Christian Leadership Training of Trainer Handbook: Efforts to Achieve Graduate Profiles - Maringan Sinambela; Grecetinovitria Merliana Butar-butar; Tiffany Tamba; Antonius Series (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
Profiles of IAKN Tarutung Christian Leadership Department Graduates are trainers, administrators and researchers. In the description of the graduate profile, the trainer is described that a trainer has the competence to carry out leadership training in religious institutions, non-governmental organizations, government agencies and the business/industrial world. Innature, efforts to achieve graduate profiles of researchers seek to equip students to have trainer skills through the Christian Leadership Training of Trainers Guidebook at the IAKN Tarutung Christian Leadership Department. Thepurpose of this research is as follows to design an innovative Christian Leadership Training of Trainer Handbook in the Christian Leadership Department. The research method used is researchand development (R&D). Based on the results of the research, the Christian Leadership Training of Trainers Handbook in the Christian Leadership Department is worth using.